2012
DOI: 10.1063/1.4760223
|View full text |Cite
|
Sign up to set email alerts
|

Observation of spin dependent photocoductivity in InSb quantum well nanowires

Abstract: We report on the electrical detection of spin dependent photoconductivity in 500 nm wide InSb quantum well nanowires using the optical orientation of electron spins. By applying weak magnetic fields (≈200 mT), we observe a spin filtering effect of classical origin caused by spin dependent back scattering of electrons from the sidewalls. Spin dependent features in the longitudinal photovoltage decay with temperature and disappears at characteristic energy (≈50 K) consistent with the theoretical spin splitting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…, the latter one reflecting the radiation helicity. Equation (10) shows that the photon drag current consists of two contributions: one being proportional to τ p (first term in the curly brackets) and the other to the first derivative τ ′ p . It is remarkable that, while the first contribution exhibits the resonance at CR, i.e., for ω = ω c , the second one has an additional resonance at the double frequency, ω = 2ω c , where the radiation absorption does exhibit this peculiarity.…”
Section: Microscopic Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…, the latter one reflecting the radiation helicity. Equation (10) shows that the photon drag current consists of two contributions: one being proportional to τ p (first term in the curly brackets) and the other to the first derivative τ ′ p . It is remarkable that, while the first contribution exhibits the resonance at CR, i.e., for ω = ω c , the second one has an additional resonance at the double frequency, ω = 2ω c , where the radiation absorption does exhibit this peculiarity.…”
Section: Microscopic Theorymentioning
confidence: 99%
“…Whereas electronic transport in InSb/AlInSb heterostructures has been investigated in depth, less is known about their optoelectronic properties. At the same time, already the first experiments have demonstrated that the photocurrents excited by infrared/terahertz radiation give an access to the Rashba spin-splitting of the conduction band [8], results in a spin-dependent electron transport [9][10][11], prove the high polarization-dependent spin susceptibility and enhanced electron-electron exchange interaction [9]. Photoelectric effects have been also shown to be an effective way to inject spin polarized electric currents and to study the anisotropy of the band spin-splitting [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation